EFFECTS OF THIRD PARTY LOGISTICS ON SUPPLY CHAIN PERFORMANCE IN KENYA (A CASE OF EAST AFRICAN BREWERIES LIMITED COMPANY) - Bwari, Maina Mildred; Getuno, Dr. Pamela; Kiarie, Dr. David (IJRDO - Journal of Applied Management Science, 2016)
The purpose of the study was to establish the effects of 3PL on supply chain performance in East African Breweries Limited. The study specifically sought to determine the effect of inventory control, distribution management, transportation management and warehousing services on supply chain performance in East African Breweries Limited. The study adopted descriptive research design. The study targeted all the 1653 employees in EABL. The sampling frame in this study was 242 staff in procurement department, 388 in production, 357 in logistics, 108 in finance, 334 in sales & marketing and 224 in quality assurance department. The study adopted stratified random sampling technique to select the sample size of the study where the population was grouped into stratus. From each stratum the study took a 10% sample to give a sample size of 165 respondents. The study collected primary data through a questionnaire. A pilot study of the questionnaire was done prior to the actual data collection to test for validity and reliability. The questionnaire was administered to the respondents through drop and pick later method. The study generated qualitative and quantitative data. Both descriptive and inferential statistics were adopted for the study. Descriptive statistics included use of frequency distribution tables and measures of central tendency, measures of variability and measures of relative frequencies while inferential statistics included regression analysis. Data was presented using tables, charts, graphs. Inferential statistics was used to determine the relationship between the variables. The study found out that inventory control, distribution management, transportation management influenced supply chain performance to a great extent but warehousing management services influenced supply chain performance to a moderate extent. The study concluded that there is a positive and statistically significant relationship between supply chain performance and inventory control, distribution management, transportation management services provided. The study recommended that there is need to strategically analyze the needs of the company and the non-core business so as to make informed decisions of the right logistics services to outsource. There is need for the management of EABL to improve transport efficiency as this could change the overall performance of the logistics system.